Ethnomathematics Exploration on Traditional Herbal Medicine-Making Tools at Sumenep Palace - Fauziyah, Fida Dinar; Ulum, Achmad Miftachul; Marhayati, (Rangkiang Mathematics Journal, 2024)
This study aims to describe the ethnomathematics exploration of traditional herbal concoction tools at the Sumenep Madura Palace. Traditional herbal medicine is a cultural heritage originating from Madura, especially from the nobility in the Sumenep Palace. This study uses a qualitative approach with ethnographic research. Data collection techniques are observation, interviews, field notes, and documentation. The results showed that in the process of making traditional herbal medicine, a mathematical concept was found, namely the concept of value comparison. Meanwhile, the money instruments used to concoct herbal medicine, namely pipisan, gandik, botekan and cengkelek, found the concept of geometry, sequence patterns and arithmetic series.